Three mammal species distinction through the analysis of scats chemical composition provided by comprehensive two-dimensional gas chromatography - Saraiva, Maria J.
In the last years, new approaches use scats analysis in ecological studies, like gas chromatographic techniques, has been developed. The aim of this study is to use VOCs (volatile organic compounds) released from scats to distinguish three mammal species: the ungulates red and fallow deer and the carnivore Eurasian otter through the application of SPME/GC??GC-ToFMS. This chromatographic technique has never been used in ecological studies. Chromatogram contour plot was effective in distinguishing between the carnivore Eurasian otter and the two ungulates. Additionally, a subset of 21 selected compounds, including hydrocarbons, ketones, aldehydes, alcohols and terpenes, allowed a distinction between Eurasian otter, red deer and fallow deer. Eurasian otter scats were characterized mainly by the presence of aldehydes that may arise from oxidative degradation of unsaturated fatty acids present in fish species, included in their diet. Red deer volatile profile is characterized by terpenes compounds, presumably related with diet, while fallow deer achieved also chemical communication markers: 2-propanone and hexane. The scat volatile profiles provide information that explains their odour and also the type of diet (herbivorous or carnivorous) and intra-specific communication through chemical signals. Being able to distinguish species using the proposed methodology is an asset to wildlife ecology and management studies.